Static and dynamic analysis of engineering structures : incorporating the boundary element method /: incorporating the boundary element method. (2020) - Petrosian, Levon G (Levon Gregory), 1952-; Ambart︠s︡umi︠a︡n, V. A (Vladimir Aleksandrovich)
No abstract available